Identification through heteroscedasticity within the network connectedness framework: The \Systemic Five" stock markets - Uluceviz, Erhan (İstanbul Bilgi Üniversitesi, 2015)
[Abstract Not Available]
Ağ bağlanmışlık çerçevesinde ayrı varyans kullanımı ile belirleme: "Sistemik Beşli" hisse senedi piyasaları